Massage Therapy for Cervical Degenerative Disc Disease: Alleviating a Pain in the Neck? - Avery, BA, RMT, Rhonda-Marie (International Journal of Therapeutic Massage & Bodywork, 2012)
Background: A 66-year-old female client with cervical degenerative disc disease at lateral left facet joint C6/C7 was experiencing symptoms of chronic neck pain accompanied by limited cervical range of motion, as well as radicular left shoulder and arm pain. The objective of this case report was to describe the effect of therapeutic massage on the client’s symptoms and impairments of cervical DDD.Methods: Therapeutic massage interventions included soft-tissue manipulation using petrissage and neuromuscular techniques, fascial work, facilitated stretching, joint play, hydrotherapy, education on self-stretching, and positive guidance about condition management. Assessment included pain-free cervical ROM and a subjective verbal pain scale.Results: After several treatment sessions, client’s symptoms had decreased and cervical ROM had improved moderately. There was also a decrease in reported pain and an increase in functional daily activities. Client showed a greater understanding of the physiologic barriers which degenerative changes may present.Conclusions: This client responded favorably to massage therapy as a treatment intervention for cervical DDD symptoms.